Fibroblast Activation Protein (FAP) specific PET for advanced target volume delineation in glioblastoma - Windisch, Paul; Röhrich, Manuel; Regnery, Sebastian; Tonndorf-Martini, Eric; Held, Thomas; Uzun-Lang, Kristin; Bernhardt, Denise; Rieken, Stefan; Giesel, Frederik L.; Haberkorn, Uwe; Debus, Jürgen; Adeberg, Sebastian (Radiotherapy and oncology, 2020)
Fibroblast Activation Protein (FAP)-specific Positron Emission Tomography (PET) has shown promising results in various cancers. This pilot study compares FAP-specific PET to MRI for treatment planning in 13 Glioblastoma patients. The resulting incongruent volumes could provide additional information for radiotherapy or biopsy planning.